The effect of microorganisms, manure, and citronella on the Pb and Cd content in heavy metal-contaminated soil and potato yields - Tamad; Maryanto, Joko; Saparso; Kurniawan, Ruli Eko Kusuma; Surono; Hanifa, Hana; Leana, Ni Wayan Anik; Amar, Haidar; Raharjo, Hardi Rahmat (Brawijaya University, 2026)
The Dieng region in Central Java, Indonesia, is a major horticulture commodities center, covering approximately 3,000 hectares of Andisols. Since the 1980s, long-term use of organic and inorganic fertilizers as well as pesticides has led to the accumulation of heavy metals, such as lead (Pb) and cadmium (Cd). Pb contents in Andisols generally remain below the Environmental Protection Agency (EPA) standard, except in Sikunang, and Cd exceeds the standard in both Sembungan and Jojogan Wonosobo. In potato tubers, Pb content exceeds the SNI 7378-2009 threshold in Wonosobo and Pekasiran Banjarnegara, while tubers from other areas are below standard. The Cd content in tubers from Jojodan and Kalilembu Wonosobo, as well as Pekasiran and Kepakisan Banjarnegara, also surpasses the standard, but in other areas, it is below standard. The use of remediators composed of chicken manure enriched with Pseudomonas sp, Dark Septate Endophytes (DSE), and Citronella (Cymbopogon nardus) as phytoremediators reduced Pb and Cd levels in both soil and potato tubers. Therefore, the best remediation strategy for mitigating heavy metal contamination included the combination of Pseudomonas sp., DSE, and citronella. These treatments did not significantly affect potato yield. The correlation among variables shows that Pb and Cd levels in potato tubers were influenced by the respective soil concentrations. However, no correlation was observed between soil heavy metal content and tuber yield.